Perlindungan Hak Konsumen dalam Jual Beli Online: Analisis Prinsip Khiyār dalam Fikih Muamalah dan Relevansinya dengan Hukum Indonesia - Achmad Alfian Saputra; Nailan Nabila (Journal of Islamic Economic Studies, 2025)
The development of digital technology has changed transaction patterns from conventional to online buying and selling, which presents both opportunities and risks for consumers. Issues such as defective goods, mismatched descriptions, and difficulties in returns indicate the need for stronger legal protection. In muamalah fiqh, the principle of khiyār gives the transacting parties the right to continue or cancel a contract based on certain conditions, including khiyār kondisi, khiyār majlis, khiyār aib, and khiyār ru’yah. This study aims to analyze the relevance of the principle of khiyār as a basis for consumer protection in online buying and selling and examine its compliance with Indonesian positive law. The research method used is descriptive qualitative with a literature study approach and normative-comparative analysis. Data sources consist of classical fiqh literature, laws and regulations, and previous research results. The results of the analysis show that khiyār aib and khiyār ru’yah are highly relevant in the context of e-commerce, because they provide the basis for consumer rights to return and refund. The integration of the principles of khiyār and Law Number 8 of 1999 strengthens consumer protection both legally and ethically. This study concludes that the implementation of khiyār can complement positive law, increase consumer awareness, and encourage fairer and more transparent online business practices.